2020
DOI: 10.3389/fpls.2020.607102
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Salinity Stress on Seeds Minerals, Storage Proteins, Fatty Acids, and Squalene Composition of New Quinoa Genotype, Grown in Hyper-Arid Desert Environments

Abstract: The effects of climate change and soil salinization on dryland ecosystems are already widespread, and ensuring food security is a crucial challenge. In this article, we demonstrate changes in growth performance and seed quality of a new high-yielding quinoa genotype (Q5) exposed to sodium chloride (NaCl), sodium sulfate (Na2SO4), and mixed salts (NaCl + Na2SO4). Differential responses to salt stress in growth performance, seed yield, and seed quality were identified. High salinity (mixed Na2SO4 + NaCl) reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Then, 50 mg of freeze-dried sample were macerated with an acidic mixture comprising 2 mL hydrochloric acid (6 M HCl), 1 mL anhydrous trifluoroacetic acid (TFA), and 0.5% 2-mercaptoethanol (2-ME). Hydrolysis was done for 40 min at 170 °C under N 2 in sealed ampules [ 41 ]. The obtained hydrolysate was dried out with an evaporator, dissolved in distilled water (1 mL), and centrifuged (12,000 rpm, 2 min, 4 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Then, 50 mg of freeze-dried sample were macerated with an acidic mixture comprising 2 mL hydrochloric acid (6 M HCl), 1 mL anhydrous trifluoroacetic acid (TFA), and 0.5% 2-mercaptoethanol (2-ME). Hydrolysis was done for 40 min at 170 °C under N 2 in sealed ampules [ 41 ]. The obtained hydrolysate was dried out with an evaporator, dissolved in distilled water (1 mL), and centrifuged (12,000 rpm, 2 min, 4 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the EAAs were not negatively affected by salinity in "Q5", a new salt-and drought-tolerant line, except for tyrosine (Toderich et al, 2020). Aloisi et al (2016) found variations in genotype response to saline conditions.…”
Section: Protein Content and Amino Acid Compositionmentioning
confidence: 89%
“…In different countries around the world, farmers and researchers have been trying to find, test and introduce nutritionally valuable seed crops that would be suitable for diverse growing conditions, achieve satisfactory yields, and offer versatile applications in food production and consumption (Gardner et al, 2019;Toderich et al, 2020;Habiyaremye et al, 2022).…”
Section: Quinoa's Adaptability To a Diverse Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil content measured in the same genotypes when irrigated with seawater (EC w > 39 dS/m) was higher and reached 39.4% (ICBA-9) [ 56 ]. Salinity stress does not only affect the oil content but also the fatty acids composition [ 86 , 87 , 88 ]. The oil is rich in USFA with LA (C18:2 ω6) being the most abundant fatty acid followed by OA (C18:1 ω9).…”
Section: Discussionmentioning
confidence: 99%